Cost‐of‐illness study for axillary hyperhidrosis in Japan. Issue 10 (9th July 2021) - Murota, Hiroyuki; Fujimoto, Tomoko; Oshima, Yuichiro; Tamada, Yasuhiko; Yanagishita, Takeshi; Murayama, Naoya; Inoue, Sachie; Okatsu, Hiromichi; Miyama, Hiroshi; Yokozeki, Hiroo
Abstract: The prevalence of primary axillary hyperhidrosis in Japan is 5.75% (males, 6.60%; females, 4.72%) in the population aged 5–64 years. No study on comprehensively evaluated direct medical costs, hygiene product costs, and productivity loss in axillary hyperhidrosis patients has been published in Japan. The aim of this study was to estimate the cost of illness for axillary hyperhidrosis in Japan by conducting a nationwide insurance claims database analysis and a cross‐sectional Web‐based survey. Among patients diagnosed with primary axillary hyperhidrosis at least once between November 2012 and October 2019, health insurance receipt data of 1447 patients were analyzed. A cross‐sectional Web‐based survey was conducted on 321 patients aged 16–59 years with axillary hyperhidrosis to calculate hygiene product costs and productivity loss using a Work Productivity and Activity Impairment questionnaire. Furthermore, nationwide estimation was performed for the hygiene product costs and productivity loss based on the number of patients estimated from the prevalence. The annual direct medical costs per axillary hyperhidrosis patient were ¥91 491 in 2016, ¥93 155 in 2017, and ¥75 036 in 2018. In all of these years, botulinum toxin type A injection accounted for approximately 90% of the total costs. The annual total cost of hygiene products per axillary hyperhidrosis patient was ¥9325. The overall work impairment (%) of working patients with axillary hyperhidrosis was 30.52%, and its monthly productivity loss was ¥120 593/patient. The activity impairment (%) of full‐time housewives with axillary hyperhidrosis was 49.05% and its monthly productivity loss was ¥176 368/patient. The annual hygiene product cost based on the nationwide estimation was ¥24.5 billion and the monthly productivity loss was ¥312 billion. The significant cost associated with axillary hyperhidrosis was clarified. If out‐of‐pocket expenses for treatments not covered by health insurance are included in the estimation, the cost will further increase.